The Construction Learning Model of Islamic Education in Society 5.0 and Its Relevance at Islamic Boarding Schools on Java Island - Nur Afif; Abd Aziz; Fatkhul Mubin (TARBIYA: Journal of Education in Muslim Society, 2023)
AbstractThe study aimed to determine the urgency of digitizing Islamic boarding school education in Society 5.0 and the effectiveness of the IT-based collaborative learning model on the creative thinking abilities of students in Islamic boarding schools on the island of Java. This mixed methods research method combines two previously existing forms of research, namely qualitative research and quantitative research. The population referred to in this research were all class X students in Islamic boarding schools on the island of Java, including Islamic boarding schools in Banten and Islamic boarding schools in East Java. The variables of this research are the IT-based collaborative learning model and creative thinking abilities. Based on the results of data analysis, it was concluded that 1) urgency digitizing Islamic boarding school education in Society 5.0 is one of the efforts that must be made for all Islamic boarding schools, especially Islamic boarding schools on the Island of Java; 2) Collaborative learning model was very effective for improving students' creative thinking abilities. All aspects of creative thinking can be developed through IT-based collaborative learning in facing Society 5.0 in Islamic boarding schools on the island of Java.AbstrakPenelitian ini bertujuan untuk menentukan urgensi digitalisasi pendidikan pesantren di dalam Masyarakat 5.0 dan efektivitas model pembelajaran kolaboratif berbasis IT terhadap kemampuan berpikir kreatif siswa di pesantren di pulau Jawa. Metode penelitian campuran ini menggabungkan dua bentuk penelitian yang sebelumnya ada, yaitu penelitian kualitatif dan penelitian kuantitatif. Populasi yang dimaksud dalam penelitian ini adalah semua siswa kelas X di pesantren di pulau Jawa, termasuk pesantren di Banten dan pesantren di Jawa Timur. Variabel penelitian ini adalah model pembelajaran kolaboratif berbasis IT dan kemampuan berpikir kreatif. Berdasarkan hasil analisis data, disimpulkan bahwa 1) urgensi digitalisasi pendidikan pesantren di dalam Masyarakat 5.0 adalah salah satu upaya yang harus dilakukan untuk semua pesantren, khususnya pesantren di Pulau Jawa; 2) Model pembelajaran kolaboratif sangat efektif untuk meningkatkan kemampuan berpikir kreatif siswa. Semua aspek berpikir kreatif dapat dikembangkan melalui pembelajaran kolaboratif berbasis IT dalam menghadapi Masyarakat 5.0 di pesantren di pulau Jawa.How to Cite: Afif, N., Aziz, A., Mubin, F. (2023) The Construction Learning Model of Islamic Education in Society 5.0 and Its Relevance at  Islamic Boarding Schools on Java Island. TARBIYA: Journal of Education in Muslim Society, 10(1), 69-84. doi:10.15408/tjems.v10i1. 35967.